2020
DOI: 10.1080/21505594.2020.1776979
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Pseudomonas aeruginosa infection by INP0341, a salicylidene acylhydrazide, in a murine model of keratitis

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen and a major cause of corneal infections worldwide. The bacterium secretes several toxins through its type III secretion system (T3SS) to subvert host immune responses. In addition, it is armed with intrinsic as well as acquired antibiotic resistance mechanisms that make treatment a significant challenge and new therapeutic interventions are needed. Type III secretion inhibitors have been studied as an alternative or in accompaniment to traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Many SAs have also been shown to modulate the expression or genetic regulation of T3SS components and effectors – a possible explanation for the disparity in phenotypic results. Although these inhibitors, like INP0341 [ 264 ], have shown recent successes in vitro and in vivo, they were excluded from this review as they have yet to be shown as direct inhibitors of the T3SS.…”
Section: Discussionmentioning
confidence: 99%
“…Many SAs have also been shown to modulate the expression or genetic regulation of T3SS components and effectors – a possible explanation for the disparity in phenotypic results. Although these inhibitors, like INP0341 [ 264 ], have shown recent successes in vitro and in vivo, they were excluded from this review as they have yet to be shown as direct inhibitors of the T3SS.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR was done on ABI PRISM 7900HT Sequence Detection System (Applied Biosystems, Grand Island, NY) using the SYBR Green PCR Master Mix (Thermo Scientific, Waltham, MA). The primers used have been described earlier (Sharma et al, 2018; Sharma, Elofsson, & Roy, 2020). Relative quantities of mRNA expression of respective genes were normalised using the 2 −ΔΔct method using GAPDH as the housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%
“…( Felise et al, 2008 ). Recently Sharma et al (2020 ) have shown that INP0341, a salicyledene acylhydrazide that blocks T3SS, effectively inhibits Pseudomonas infection in a murine model of keratitis. The salicyledene acylhydrazides block the T3SS in several pathogens, including Y. pseudotuberculosis ( Nordfelth et al, 2005 ; Bailey et al, 2007 ), C. trachomatis ( Slepenkin et al, 2011 ) , S. enterica , and P. aeruginosa.…”
Section: Other Compoundsmentioning
confidence: 99%